2014
DOI: 10.14411/eje.2014.046
|View full text |Cite
|
Sign up to set email alerts
|

Stage specific consumption and utilization of aphids, conspecific and heterospecific eggs by two species of Coccinella (Coleoptera: Coccinellidae)

Abstract: Abstract. The nutritive quality of aphids, conspecific and heterospecific eggs as food for ladybirds is a controversial issue. If ladybirds find aphids more palatable than eggs then they are more likely to efficiently exploit and be biocontrol agents of aphids. If eggs of conspecific or heterospecific ladybirds are more palatable than aphids these biocontrol agents may either impede aphid pest suppression or become a threat to other species of ladybirds. Thus, prior to formulating predatory guilds of ladybirds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…2011, 2012; Kumar et al . 2013, 2014a; Bista and Omkar 2014; Keshavarz et al . 2015; Rakhshan and Ahmad 2015).…”
Section: Introductionmentioning
confidence: 99%
“…2011, 2012; Kumar et al . 2013, 2014a; Bista and Omkar 2014; Keshavarz et al . 2015; Rakhshan and Ahmad 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A similar study in Coccinella undecimpunctata L. (Bayoumy et al, 2016) reported shorter offspring developmental duration (by accelerating pupation) when both the parents cannibalized eggs. Earlier studies in coccinellids have shown stage-specific (Bayoumy and Michaud, 2015a; Bayoumy et al, 2016; Omkar et al, 2004; Kumar et al, 2014) benefit of cannibalism. In Coleomegilla maculata Lengi (Gagne et al, 2002) cannibalism by second instar larvae resulted in shorter development duration and better larval growth than non-cannibal.…”
Section: Discussionmentioning
confidence: 98%
“…In predatory guilds, small ladybirds are more easily deterred from foraging possibly because they are more vulnerable to intraguild predation (Kumar et al 2014b). The fitness parameters, particularly growth-rate and conversion-efficiency, of small ladybirds even declines due to reduced foraging in habitats previously visited by other predators (Kumar et al 2014a).…”
Section: Effect Of Footprints / Foraging Deterrent Pheromonesmentioning
confidence: 99%